Long-Term Mechanical Durability of Left Ventricular Assist Devices: An Urgent Call for Periodic Assessment of Technical Integrity. Issue 4 (July 2018) - Muslem, Rahatullah; Akin, Sakir; Constantinescu, Alina A.; Manintveld, Olivier; Brugts, Jasper J.; van der Heiden, Cees W.; Birim, Ozcan; Bogers, Ad J. J. C.; Caliskan, Kadir
Abstract : Long-term durability and incidence of potential mechanical device failure (MDF) are largely unknown. In this study, we investigated the incidence and potential predictors of MDF in continuous flow left ventricular assist device (CF-LVAD) patients. We conducted a retrospective study of all CF-LVADs (type HeartMate II) implanted in our center. MDF was defined as a failure of driveline, inflow–outflow graft, electrical power, drive unit, or motor failure, excluding device failure because of a biologic complication ( e.g., device thrombosis, hemolysis, or infections). A total of 69 CF-LVADs were implanted in 59 patients (median support time 344 days [interquartile range IQR, 149–712 days], mean age 50.1 ± 10.7 years, 75% male). MDF occurred in 9 (13%) CF-LVAD patients at a median follow-up time of 846 (IQR, 708–1337) days after implantation. Freedom of MDF through the first, second, and third year after LVAD implantation was 100%, 85%, and 64%, respectively. Patients who experienced MDF were significantly longer supported by their LVAD (median 846 [IQR, 708–1337] vs 268 [IQR, 103–481] days; p = 0.001) and were more frequently readmitted because of LVAD-related technical problems ( p = 0.002), including a higher rate of LVAD controllers exchange (44% vs 12%, respectively; p = 0.03). The main reason for MDF was a damaged or fractured driveline (n=8, 89%). In 2 patients, sudden death was related to MDF. Patients needing extended CF-LVAD support are at increasing risk for MDF. Various technical problems precede the onset of MDF. Periodical extensive assessment of the technical integrity of the device is urgently needed during long-term LVAD support.